Socioeconomic disparities in use of rhythm control therapies in patients with incident atrial fibrillation: A Finnish nationwide cohort study - Teppo Konsta; Jaakkola Jussi; Biancari Fausto; Halminen Olli; Linna Miika; Haukka Jari; Putaala Jukka; Mustonen Pirjo; Kinnunen Janne; Luojus Alex; Itäinen-Stromberg Saga; Hartikainen Juha; et al. (ELSEVIER IRELAND LTD, 2022)
Background:
In patients with atrial fibrillation (AF), socioeconomic disparities have been reported in the use of
oral anticoagulant therapy and outcomes, but whether income also affects the utilization of antiarrhythmic
therapies (AATs) for rhythm control is unknown. We assessed the hypothesis that AF patients with higher income are more likely to receive AATs.
Methods:
The nationwide retrospective registry based FinACAF cohort study covers all patients with AF from all
levels of care in Finland. Patients were divided in AF diagnosis year and age-group specific income quintiles according to their highest annual income during 2004–2018. The primary outcome was the use of any AAT, including cardioversion, catheter ablation, and fulfilled antiarrhythmic drug (AAD) prescription.
Results:
We identified 188 175 patients (mean age 72.6 ± 13.0 years; 49.6% female) with incident AF during
2010–2018. Patients in higher income quintiles had consistently higher use of all AAT modalities. When
compared to patients in the lowest income quintile, the adjusted incidence rate ratios (95% CI) in the highest quintile were 1.53 (1.48–1.59) for any AAT, 1.71 (1.61–1.81) for AADs, 1.43 (1.37–1.49) for cardioversion, and 2.00 (1.76–2.27) for catheter ablation. No temporal change during study period was observed in the magnitude of income disparities in AAT use, except for a decrease in income-related differences in the use of AADs.
Conclusion: Profound income-related disparities exist in AAT use among patients with AF in Finland, especially in the use catheter ablation.